EXPLORING THE IMPLEMENTATION OF HOLIDAY CONVERSATION LEARNING THROUGH HEUTAGOGY AND DIGITAL MEDIA IN ELEMENTARY SCHOOLS - Aisyah Yasmin Azizah; Yuliyanto Sabat; Sulistyaningsih; Eka Fadilah (Universitas Muhammadiyah Makassar, 2026)
This study aims to explore the implementation of Holiday Conversation learning through a heutagogical approach supported by digital media and to examine its impact on students’ speaking skills and learner autonomy at the elementary school level. The urgency of this research lies in the persistence of teacher-centered English speaking instruction in elementary schools, which limits students’ confidence, autonomy, and opportunities for meaningful oral communication despite the increasing availability of digital learning media. The novelty of this study is the integration of heutagogy as a self-determined learning approach with digital platforms such as YouTube and Wordwall specifically for elementary-level English speaking instruction, an area that remains underexplored in previous studies. This research employed a descriptive qualitative design and was conducted at MI Ketegan, Sidoarjo, East Java, Indonesia, involving 24 fifth-grade students from the International Class Program (ICP). Data were collected through participatory classroom observations, documentation of students’ learning products, and teacher reflection notes. The data were analyzed descriptively using data triangulation to ensure credibility and trustworthiness. The findings indicate that the heutagogy-based digital learning approach effectively enhanced students’ speaking skills, including fluency, vocabulary use, grammatical accuracy, and self-confidence. In addition, the learning process fostered learner autonomy by encouraging students’ learning initiative, decision-making ability, collaboration, and reflective learning behaviors. In conclusion, this study contributes empirical evidence to elementary English language education by demonstrating that heutagogical, digitally supported speaking instruction creates a meaningful learning environment that strengthens both communicative competence and learner autonomy.